Correction: Adragna et al. State-of-the-Art Power Factor Correction: An Industry Perspective. Encyclopedia 2024, 4, 1324–1354 - Claudio Adragna; Alberto Bianco; Giovanni Gritti; Matteo Sucameli (Encyclopedia)
The authors would like to make the following corrections to the originally published paper [...]